A unique presentation of IgG4 disease with ocular, neurologic and mastoid involvement. Issue 11 (14th November 2022) - Narotam Jeena, Heena; Afrogheh, Amir; West, Joshua; van der Colff, Freddie; Brey, Naeem
Abstract : A man in his 20s presented with headache and acute deterioration in visual acuity. He was found to have panuveitis and raised intracranial pressure with papilloedema. MRI and F-fluorodeoxyglucose positron emission tomography confirmed a subclinical, but active, inflammatory mastoid process. Histology of the mastoid showed immunoglobulin G4 (IgG4) cells, plasma cells and storiform fibrosis. This presentation of IgG4 disease has not been previously described. Treatment with high-dose steroids was initiated, followed by long-term immunosuppressive therapy. The patient's symptoms improved, although he remains dependent on azathioprine and low dose oral steroids for symptom control. To date, there has been no progression of the disease.